Air‐Assisted Transient Synthesis of Metastable Nickel Oxide Boosting Alkaline Fuel Oxidation Reaction. Issue 46 (7th October 2020) - Liu, Chang; Zhou, Wei; Zhang, Jinfeng; Chen, Zelin; Liu, Siliang; Zhang, Yang; Yang, Jiaxing; Xu, Lianyong; Hu, Wenbin; Chen, Yanan; Deng, Yida
Abstract: Construction of active and durable non‐noble‐metals based electrocatalysts is one of important requirements for the practical application and development of fuel cells, which are presently inhibited by relative sluggish charge transport and reaction kinetics. Herein, highly dispersed ultrathin carbon‐coated nickel oxide nanoparticles settled on carbon cloth (NiO@C/CC) as efficient catalysts for alkaline fuels oxidation are synthesized via an air‐assisted transient thermal shock strategy. This NiO@C/CC catalyst induces an outstanding catalytic activity (up to 119.1 mA cm −2 ) and durability (a little current decay during tests) in electrooxidation for ethanol, even for methanol and ethylene glycol, which outperforms most of the reported non‐noble metal catalysts. The excellent catalytic performance of NiO@C/CC is essentially attributed to the oxygen vacancies, high concentration, high‐valence‐state Ni, and carbon layers of NiO@C NPs, which contribute to regulate the surface properties and electronic structure, enhance charge transfer, and provide abundant active sites, promoting adsorption capacity of reactant molecules on its surface. The facile and promising air‐assisted transient thermal shock strategy can be extended to guide rational design and rapid synthesis of transition metal compounds as advanced catalysts for alkaline direct alcohol fuel cells. Abstract : A metastable NiO nanomaterial is fabricated via air‐assisted thermal shock technique (ATS‐tech) to boost electro‐oxidation performance of alcohols in alkaline media. The oxygen vacancies, high concentration of Ni 3+ species, and the ultrathin carbon‐coated structure in NiO@C/CC raise adsorption capacity, enhance electron conductivity, provide more active sites, confine the nanoparticles, respectively, and they all contribute to the improvement of electrocatalytic performance.